Pengaruh Lokasi Les terhadap Kepuasan Orang Tua: Studi Kasus Les di Rumah Versus di Gereja di Desa Laman Baru (Jurnal Pendidikan Agama dan Teologi, 2025)
This study was conducted with the primary objective of examining in depth the influence of lesson venue on parents’ satisfaction in Laman Baru Village. The research focused on comparing two alternative locations that have been options for the community: conducting lessons in residents’ homes on a rotating basis and conducting lessons in the church. Each of these alternatives carries different characteristics in terms of comfort, symbolic meaning, as well as social and religious acceptance within the local community. The research method employed was a descriptive quantitative approach using questionnaires and field observations. Through this method, the researcher was able to obtain empirical data that reflected parents’ perceptions and real experiences regarding lesson venues. The collected data were then analyzed to determine the extent to which location affected satisfaction, comfort, sense of security, and parents’ involvement in supporting their children’s nonformal education activities. The findings revealed that the choice of venue significantly influenced parents’ attitudes and responses. Lessons conducted in residents’ homes were perceived as more inclusive, since they embodied a sense of togetherness and collective participation within the community. Furthermore, this venue was considered symbolically neutral, thus avoiding any impression of favoritism toward a particular religious group. It also opened wider opportunities for parents to be directly involved in supporting their children. On the other hand, lessons held in the church created resistance, particularly among non-Christian parents, who viewed the church as a less neutral venue laden with specific religious meaning. This condition potentially reduced the participation of certain community members and generated discomfort in a multicultural context. Therefore, these findings highlight the importance of considering social, economic, and religious sensitivities in determining the venue of nonformal education, so that the activities carried out can be broadly accepted and bring optimal benefits to the entire community.